ANALISIS PENYELESAIAN SENGKETA KONSTRUKSI DI INDONESIA - Lature, Karolus Elwinman (Jurnal Legislasi Indonesia, 2018)
Nowadays, Indonesia is faced to the phenomenon of equitable development. President Joko Widodo is building infrastructure projects intensively to remote areas. Indirectly it makes the construction service as one of the six sectors that contribute to the Indonesian economy. The concern is that construction disputes are rising in line with the intensity of this development. However, construction disputes are still a serious problem in some countries. This problem is able to overcome under Law No. 2 Year 2017 on Construction Services. Since the implementation rules mandated by this law have not yet been published, this research needs to be done in order to avoid the formation of regulations from misperception. Therefore, this study contains the author's normative analysis of the philosophy and dispute resolution mechanism of construction in Indonesia after the issuance of Law No. 2 Year 2017 on Construction Services.